Problem Tauhid dalam Ritual Nyadran, Sidoarjo: Perspektif Fakhrudin Ar-Razi - Muttaqin Muttaqin; Ainul Fuad Fitriansyah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
Muslims in Java are very familiar with the various terms of gratitude events. This event or ritual is commonly known as ‘selametan’. The ‘selametan’ ritual has various names. ‘Selametan’ is one of the Javanese customs that is still preserved (‘diuri-uri’) by several people. This article aimed to analyze the implementation of the Nyadran ritual in Balongdowo, Sidoarjo. The problem discussed about the practice of shirk contained in the Nyadran singkritis ritual. To achieve this goal, the authors uses descriptive and critical analysis methods. While the research approach is theological. The concept of tawhid (theological approach) became the basis for assessing shirk in this ritual. The results of the study reveal the fact that the Nyadran ritual in the village of Balongdowo, Sidoarjo is still contains shirk values that affect the spirituality of Muslims. This can be seen from several activities, namely; procession of eating together, visiting the tomb of Dewi Sekardadu who is she believed to be the mother of one of the Walisongo, namely Sunan Giri. In addition, several series of these rituals still believe in the existence of magical powers or the power of the unseen nature so that they are still full of polytheistic values, which can influence the spirituality of Muslims and their monotheism (’tauhid’).